The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1461-0248.2007.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Growth Rate vs. Geochemical Hypothesis for latitudinal variation in plant nutrients

Abstract: Two hypotheses have been proposed to explain increases in plant nitrogen (N) and phosphorus (P) concentrations with latitude: (i) geochemical limitation to P availability in the tropics and (ii) temperature driven variation in growth rate, where greater growth rates (requiring greater nutrient levels) are needed to complete growth and reproduction within shorter growing seasons in temperate than tropical climates. These two hypotheses were assessed in one forest type, intertidal mangroves, using fertilized plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
103
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 56 publications
(109 reference statements)
19
103
4
Order By: Relevance
“…In fact, not all the studies have detected general patterns of leaf N:P content ratios between and within the climate areas (Lovelock et al 2007, Townsend et al 2007, Vitousek et al 2010 and there are soil chronosequence studies that have observed that soil available-P was greater in the intermediate ages than in the young and old ages within the time sequence (Crews et al 1995. The average of leaf N:P content ratios observed in Hawaii plants (21.6 6 1.0) and in Borneo plants, (21.8 6 0.7) are high compared to other studies for woody plants throughout the world that report an average leaf N:P content ratio between 14 and 16 (Koerselman andMeuleman 1996, Gü sewell andBollens 2003).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, not all the studies have detected general patterns of leaf N:P content ratios between and within the climate areas (Lovelock et al 2007, Townsend et al 2007, Vitousek et al 2010 and there are soil chronosequence studies that have observed that soil available-P was greater in the intermediate ages than in the young and old ages within the time sequence (Crews et al 1995. The average of leaf N:P content ratios observed in Hawaii plants (21.6 6 1.0) and in Borneo plants, (21.8 6 0.7) are high compared to other studies for woody plants throughout the world that report an average leaf N:P content ratio between 14 and 16 (Koerselman andMeuleman 1996, Gü sewell andBollens 2003).…”
Section: Discussionmentioning
confidence: 96%
“…v www.esajournals.org ships are observed between leaf N:P content ratios and either latitude or annual mean precipitation within the tropical area (Townsend et al 2007, Lovelock et al 2007. He et al (2008) investigated the changes of N:P ratios of 213 plant species across 199 research sites located in a climatic gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean N concentration in plant tissues was greater in plants grown at higher nutrient availability levels than in control treatments. Nitrogen is an essential component of all enzymes and phosphorus is vital for protein synthesis forming an essential component of RNA (Lovelock et al, 2007). The concentration of N and P in tissues also influences the rates of ecological processes, for example, grazing, parasitism and decomposition have been observed to be influenced by the stoichiometery of N and P within tissues (Lovelock et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At their latitudinal limits of occurrence frost is added to the environmental constraints for mangrove establishment, survival, and structural development (Lugo and Zucca, 1977;McMillan and Sherrod, 1986;Lovelock et al, 2007;Soares et al, 2012).…”
Section: Introductionmentioning
confidence: 99%